2007
DOI: 10.1590/s0102-36162007001100002
|View full text |Cite
|
Sign up to set email alerts
|

Medidas de avaliação de qualidade de vida e estados de saúde em ortopedia

Abstract: mentos mais comumente utilizados na literatura internacional e aqueles disponíveis para uso no Brasil. Descritores

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
21

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 22 publications
0
19
0
21
Order By: Relevance
“…8,10,[13][14][15][16][17][18] However, several studies indicate a lack of consensus on the best way to assess these factors. 13,[19][20][21][22] The purpose of this study…”
Section: Rehabilitation Of Amputeesmentioning
confidence: 99%
“…8,10,[13][14][15][16][17][18] However, several studies indicate a lack of consensus on the best way to assess these factors. 13,[19][20][21][22] The purpose of this study…”
Section: Rehabilitation Of Amputeesmentioning
confidence: 99%
“…Sendo genérico, permite a comparação entre indivíduos com diversos diagnósticos e é amplamente usado em estudos com pessoas portadoras de diversas doenças. O SF-36 é um instrumento adequado para avaliação da qualidade de vida entre indivíduos com doenças musculoesqueléticas (LOPES et al, 2007).…”
Section: Métodounclassified
“…These parameters enable analysis on health status and disease manifestations within an individual's life from his own subjective perspective, thereby complementing the objective clinical data. 10 The improvement in health-related quality of life after primary total hip arthroplasty has been documented in several studies. [11][12][13][14][15][16][17] Concern regarding this issue among the elderly population undergoing this surgical procedure has been highlighted over recent years, 6,7,[18][19][20] 22 stand out because of their high levels of use.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Use of a generic tool, complemented by application of a specific tool to assess health-related quality of life when analyzing this type of condition, has the advantage of evaluating the patients' perception of their general health status combined with the possibility of detecting specific clinical changes to healthrelated quality of life after primary total hip arthroplasty. 8,10,28 The performance characteristics of generic and specific tools used in the elderly and general populations differ from each other. 29 Concerning the SF-36, it is important to mention that one study found that this tool is a reliable way of assessing healthrelated quality of life among elderly patients undergoing primary total hip arthroplasty.…”
Section: Introductionmentioning
confidence: 99%